Cp*Co(III)‐Catalyzed Dehydrative C2‐Prenylation of Pyrrole and Indole with Allyl Alcohols. Issue 19 (21st August 2021) - Basuli, Suchand; Sahu, Samrat; Saha, Shuvendu; Maji, Modhu Sudan
Abstract: Non‐activated allyl alcohols are utilized as allylating agent for thiocarbamate‐directed allylation of pyrrole and indole. The synthetic methodology is accompanied by advantages like silver‐free conditions and generates water as the by‐product. A wide range of substituted pyrroles and indoles along with several structurally different allyl alcohols took part in the reaction. Among notable examples, biologically relevant prenylation, geranylation, and synthesis of 1, 3‐dienes are achieved. Selective mono allylation of pyrrole, gram‐scale synthesis, and ready deprotection of directing group are the other key highlights of this method. Abstract :